Not all infantile respiratory distress in winter is bronchiolitis: congenital lobar emphysema. (24th October 2011) - Taqvi, Laura; Griksaitis, Michael; Eastham, Katherine
Abstract : The authors report the case of a 4-week-old male infant presented during the winter period with respiratory distress. He had a 3 day history of cough and coryza, and a 2 day history of breathlessness and reduced feeding. He had evidence of tachypnoea, subcostal recession and hypoxia on examination. An initial diagnosis of bronchiolitis was made. The authors explore how the correct diagnosis of congenital lobar emphysema (CLE) was reached, highlighting key clinical signs and investigations. He had evidence of a hyperinflated right middle lobe, with collapse of right upper and lower lobes and left upper lobe with associated mediastinal shift on chest x-ray (CXR) and CT scan. He was referred to the regional Paediatric Cardiothoracic Centre where right middle lobectomy was performed with complete resolution of his respiratory distress and re-expansion of the compressed lobes on CXR. Current literature concerning CLE is reviewed.